2017
DOI: 10.15537/smj.2017.5.15643
|View full text |Cite
|
Sign up to set email alerts
|

Cemento-ossifying fibroma of the mandible

Abstract: Cemento-ossifying fibromas are rare fibro-osseous benign neoplasms that affect the jaws. They are included in the group of mesodermal odontogenic tumors and commonly present as a progressively growing lesion that might attain enormous size with resultant deformity, if left untreated. A confusion prevails on the terminology, which can only be confirmed by histopathologic evaluation. A case of cemento-ossifying fibroma involving the right mandible is described in a 30 year-old female patient. The clinical, radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 17 publications
(42 reference statements)
0
37
0
8
Order By: Relevance
“…Considering the radiographic characteristics, the reported case shows well-defined mixed lesion. In general, displacements and reabsorption of the tooth roots may appear (Chang et al;Oliveira et al, 2008;El-Mofty;Bala et al), such as in the case reported. Radiographically it is also shown the displacement of the mandibular can alto the mandible base, which are characteristics that suggest a benign lesion.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Considering the radiographic characteristics, the reported case shows well-defined mixed lesion. In general, displacements and reabsorption of the tooth roots may appear (Chang et al;Oliveira et al, 2008;El-Mofty;Bala et al), such as in the case reported. Radiographically it is also shown the displacement of the mandibular can alto the mandible base, which are characteristics that suggest a benign lesion.…”
Section: Discussionmentioning
confidence: 73%
“…The early stage progresses gradually to a mixed lesion as the calcified material settles in the tumor (White & Pharoah; da Silveira et al; Bala et al). Mature lesions may consist of a dense radiopaque mass surrounded by a well-defined radiotransparent line (Titinchi & Morkel, 2016;Bala et al). Considering the radiographic characteristics, the reported case shows well-defined mixed lesion.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is more common between the third and fourth decade of life in women and occurs predominantly in the mandible. The expansive growth of the lesion can cause tooth displacement, facial asymmetry and functional impairment (Neville, et al, 2016;Bala, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the expansion capacity, the fibroma can cause asymmetries, dental displacements, and dysphagia. Since these injuries often lead to major deformities in the stomatognathic segment and can hinder or even prevent proper feeding (de Amorim, et al, 2015;Neville, et al, 2016;Bala, et al, 2017). Thus, nutritional capacity of the patient may be compromised.…”
Section: Introductionmentioning
confidence: 99%